Therapy of patients with osteoarthritis with low energy laser radiation - L. V. Vasiljeva; LA Starodubtsevu; N A Barsukova (Научно-практическая ревматология)
Objective. To assess influence oflow energy laser radiation (LELR) on glycosaminoglycan (GAG) and vitamin С level in pts with osteoarthritis (OA). Material and methods. 82 pts with primary OA and 25 healthy volunteers signed informed consent were included in an open randomized prospective 12-month study. Inclusion criteria: unsatisfactory effect of previous drug therapy (DT), stable NSAID dose 3-5 days before and during LELR course, absence of comorbid hepatic and kidney diseases in stage of functional decompensation, malignant diseases, exclusion therapy influencing microcirculation, exercise therapy, physical therapy. Intra-articular injections were not done during 3 months before the study. Pts were divided into 2 groups. Group 1 received complex DT and LELR, group 2 - DT. clinical and laboratory parameters were used as efficacy measures. Statistical analysis was performed on personal computer IBM PC (OS — Windows EP Home Edition) with Microsoft office and STATISTICA 6.0 programs. Results. Analysis of the results showed significant improvement of most measures in comparison with traditional DT. LELR administration allowed to decrease chondroprotector and NSAID doses. Vitamin С decrease in serum of OA pts may be a risk factor of development and progression of this disease.